Micronized corn and urea-liquid supplements in growing rations for calves - K. Bolsen; Leslie J. Chyba; W. Ibbetson (Kansas Agricultural Experiment Station Research Reports, 1977)
In growing rations containing fescue hay, micronized corn + urea-liquid gave: (1) 20.5% faster gains and 11.5% more efficient gains than cracked corn + urea-liquid and (2) similar rate and efficiency of gains as cracked corn + soybean meal.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station); 291; Cattlemen' s Day; 1977; Beef; Corn; Urea; Rations